Hidden problem in an elderly woman with repeated urinary tract infection: Giant megaureters resulting from a 'yo‐yo' phenomenon. Issue 3 (15th July 2013) - Huang, Po‐Wei; Cha, Tai‐Lung; Chang, Huang‐Ching; Sun, Guang‐Huan; Yu, Dah‐Shyong; Meng, En
<x xml:space="preserve">Abstract</x> An incomplete‐type ureteral duplication (IUD) is a congenital anomaly, and is usually found incidentally on imaging findings in children. Clinically, a marked megaureter is caused by a long‐term 'yo‐yo' phenomenon in IUD, and is a rare, initial suspicion in elderly people, especially when manifested through repeated urinary tract infections (UTI). We report on a 67‐year‐old woman who suffered from repeated UTI and left flank pain. IUD with marked megaureters resulting from the 'yo‐yo' phenomenon was diagnosed by a series of imaging studies. The symptoms were successfully relieved by tapering and reimplantation of the dilated ureters. Finally, we emphasize a paradoxical phenomenon in the interpretation of the effective renal plasma flow study, even if this means correcting for the pitfalls of the examination itself.